Factors associated with academic performance in first-year medical students - Jara, Delia (2008)
Introduction: The low academic performance at the university is influenced by multiple factors manifested in the early years of study. Objectives: To determine the factors affecting the low academic performance of medical students during their first year of studies. Design: Observational, longitudinal study. Non-probability sampling was used for assessments. Setting: San Fernando Faculty of Medicine, San Marcos National University, Lima-Peru. Interventions: A questionnaire, physical, psychological and laboratory examinations were applied. Main outcome measures: Factors that influence low academic performance. Results: Forty students (14 females and 26 males), aged between 18 and 30 years, were evaluated; 31 came from state schools (78%) and 9 from private schools (23%). With regards to study habits, 27 (67%) reported reading the subjects of the profession at least once a day, and 13 (33%) did so weekly. Study hours per day were 1 to 2 in 10 (25%), 3 to 4 hours in 18 (45%), 5 to 6 hours in 10 (25%). and 2 (5%) reported studying only the day of test; 25 students (62%) presented as a strategy to study only by memory, 7 (18%) used memory plus class notes, 4 (10%) used diagrams and notes, and 4 (10%) notes and diagrams and texts. The students predominant character was cheerful in 22 (55%) and not happy in 18 (45%). Self-esteem was considered high in 15 participants (37,5%), moderate in 21 (52,5%) and low in 4 (10%). The socio-economic aspect of the participants revealed that in 17 cases (42,5%) family income was equal to or less than S/ 1 500 (one thousand five hundred soles) a month, the house was own in 23 (57,5%) and rented in 17 (42,5%). House location was largely in popular areas in 25 (62,5%), followed by residential area in 10 (25%), and human settlements in 5 (12,5%). Conclusions: The students’ low academic performance in the first year of study was related to proceeding from public schools, lack of study habits and strategies, moderate to low self-esteem, low socioeconomic status, residing in popular areas without home ownership, and presenting physical ailments.